Elusive indeed – The mechanical versus psychological effects of electoral rules at the district level. (June 2018) - Harfst, Philipp; Dingler, Sarah C.; Fortin-Rittberger, Jessica; Noseck, Julian; Kosanke, Sven
Abstract: While electoral research has become one of political science's most fertile areas, to date no empirical contribution has addressed the three mechanisms of the electoral chain – strategic entry, strategic voting, and the electoral system's mechanical effect – in a unified analytical framework. This paper addresses this shortcoming by analysing the effect of electoral systems on party system size, accounting for all three mechanisms. Our study yields three major findings drawing on constituency-level data covering 462 electoral districts in Finland and Portugal between 1962 and 2011. First, macro-sociological context, measured as cleavages, operate at the district level: An increase in the heterogeneity within a constituency significantly increases party system size. Second, in the two established democracies we examine, we observe that district-level bottom-up coordination takes places. Finally, while our analyses reveal that some strategic voting takes places, it is blurred by a comparatively large amount of non-strategic behaviour by voters. The variance we find surrounding psychological effects is too large to exert a targeted impact. In sum, the mechanical effect turns out to be the most decisive link of the electoral chain.